1996
DOI: 10.1016/s0092-8674(00)81047-8
|View full text |Cite
|
Sign up to set email alerts
|

Mother Cell–Specific HO Expression in Budding Yeast Depends on the Unconventional Myosin Myo4p and Other Cytoplasmic Proteins

Abstract: Certain cell types give rise to progeny that adopt different patterns of gene expression in the absence of any differences in their environment. Cells of budding yeast give birth to mother and daughter cells that differ in that only mother cells express the HO endonuclease gene and thereby switch mating types. We describe the identification of five genes, called SHE1-SHE5, that encode cytoplasmic proteins required for mother-specific HO expression. She1p, which is identical to the minimyosin Myo4p, and She3p a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
304
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(313 citation statements)
references
References 38 publications
9
304
0
Order By: Relevance
“…Both formins promote actin cable assembly Sagot et al, 2002a), but the loss of Bnr1p causes only a mild delay in cell separation (Vallen et al, 2000), whereas the absence of Bni1p causes a widened bud neck (Jansen et al, 1996;Zahner et al, 1996;Mosch and Fink, 1997;Sheu et al, 2000), an inability to engage in tip-directed growth (Evangelista et al, 1997;Mosch and Fink, 1997;Sheu et al, 2000;Ozaki-Kuroda et al, 2001), a defect in bipolar bud site selection (Zahner et al, 1996), a partial defect in cytokinetic ring contraction (Vallen et al, 2000), a defect in early spindle alignment Lee et al, 1999), and a variety of synthetic lethal genetic interactions (Kohno et al, 1996;Longtine et al, 1996;Fujiwara et al, 1998;Fujiwara et al, 1999;Lee et al, 1999;Tong et al, 2001Tong et al, , 2004. We suggest that many, if not all, of these can be attributed to the actin assembly activity of the two formins in conjunction with their specific localizations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both formins promote actin cable assembly Sagot et al, 2002a), but the loss of Bnr1p causes only a mild delay in cell separation (Vallen et al, 2000), whereas the absence of Bni1p causes a widened bud neck (Jansen et al, 1996;Zahner et al, 1996;Mosch and Fink, 1997;Sheu et al, 2000), an inability to engage in tip-directed growth (Evangelista et al, 1997;Mosch and Fink, 1997;Sheu et al, 2000;Ozaki-Kuroda et al, 2001), a defect in bipolar bud site selection (Zahner et al, 1996), a partial defect in cytokinetic ring contraction (Vallen et al, 2000), a defect in early spindle alignment Lee et al, 1999), and a variety of synthetic lethal genetic interactions (Kohno et al, 1996;Longtine et al, 1996;Fujiwara et al, 1998;Fujiwara et al, 1999;Lee et al, 1999;Tong et al, 2001Tong et al, , 2004. We suggest that many, if not all, of these can be attributed to the actin assembly activity of the two formins in conjunction with their specific localizations.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the septins, which are polarized in both wild-type and bni1⌬ unbudded cells ( Figure S2A and B), provide the cue by which Bnr1p is weakly polarized in unbudded cells, because yeast lacking both Bni1p function and septin function are unable to initiate a normal bud ( Figure 6A). The guidance of bud emergence by this disorganized mesh of Bnr1p-dependent cables may provide an explanation for the widened neck of bni1⌬ cells (Jansen et al, 1996;Zahner et al, 1996;Mosch and Fink, 1997;Sheu et al, 2000), a feature that also may indirectly explain the cytokinetic ring contraction defects (Vallen et al, 2000), and minor defects seen in the septin ring of bni1⌬ yeast ( Figure S2A, middle bni1⌬/bni1⌬ cell).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucan synthase is involved in cell wall synthesis (Shematek and Cabib, 1980). Bni1p is known to be implicated in cytokinesis and establishment of cell polarity (Jansen et al, 1996;Zahner et al, 1996). We have moreover found that Bni1p directly interacts with pro®lin, an actin monomer-binding protein, which accelerates the polymerization of actin (Imamura et al, 1997).…”
Section: Introductionmentioning
confidence: 82%